Optimization of magnesium silica aerogel production and evaluation as a food additive: a comparative study of water glass and bio-based sodium silicate source as a precursor - Yapici, Emine; Ikizler, Burcu Karakuzu; Kececiler-Emir, Ceren; Yucel, Sevil (SPRINGER, 2025)
The current work presents the findings of production, optimization, and comparative study on chemical, structural, morphological, and water vapor adsorption properties of low-cost water glass-based magnesium silica aerogels (Mg-WG) and eco-friendly rice hull ash-based magnesium silica aerogels (Mg-RHA). The production parameters (Si: Mg molar ratio, feeding time, and aging temperature) of Mg-WG and Mg RHA were optimized using the Box-Behnken Design (BBD) technique combined with Response Surface Methodology (RSM). The optimum product was revealed according to BET surface area (SBET) and water vapor adsorption capacity (WVAC) response variables. Analysis of variance (ANOVA) showed that quadratic model is statistically significant. By optimizing the aging temperature, Si: Mg ratio, and feeding time production parameters of Mg-WG and Mg-RHA, the optimum production conditions are 75 degrees C and 74.87 degrees C aging temperature, 1.99 and 1.08 Si: Mg ratio, and 5 min and 7.65 min feeding times were determined respectively. The optimum production conditions of Mg-WG and Mg-RHA were determined as 75 degrees C and 74.87 degrees C aging temperature, 1.99 and 1.08 Si: Mg ratio, and 5 min and 7.65 min feeding time, respectively. The effect of Mg silica aerogel added to food powders on the flowability was investigated with a powder flow tester. The results revealed that the use of Mg silica aerogel improved the flow behavior of rock salt and acted as an anti-caking agent. It has been observed that application doses above 50 mg/ml for Mg-WG aerogels and 50 mg/ml and above for Mg-RHA aerogels have a cytotoxic effect on HEK-293 cells and cell viability decreases. Furthermore, it was determined that Mg silica aerogels did not cause any toxic effects in in vitro cytotoxicity and in vivo acute systemic toxicity in appropriate doses. Waste of rice hull ash was used during the magnesium silica aerogel production.Magnesium silica aerogel production process optimized by response surface methodology.Flowability behavior in food powder was evaluated by PFT for use as anticaking agent.In vitro and in vivo toxicity studies revealed no toxic effects of magnesium silica aerogels in appropriate doses.
Keywords: Anti-caking agent; Magnesium silica aerogel; Rice hull ash; Response surface methodology; Spray drying; PHYSICOCHEMICAL PROPERTIES; ALUMINUM SILICATE; SURFACE-AREA; ADSORPTION; PARAMETERS; TOXICITY; SORPTION; POWDER; CAKING; SAFETY; Materials Science